TRACES OF SUSTAINABILITY PRINCIPLES IN ARCHITECTURE TEACHING PROGRAMS AT SALAHADDIN UNIVERSITY SURVEY AND ANALYSIS OF TEACHING COURSE BOOKS - AHMED, CHRA HUNAR; KHAYAT, MAHMOOD AHMED (Journal of Duhok University, 2017)
The rising importance of the theory and principles of sustainability, and its high influence on architecture practice and education is very clear in a way that the term sustainable has been mentioned many times in the UIA UNESCO charter for architectural education (UIA, 2015), it is clearly stated (Architecture for a Sustainable Future) as one of its aims for architecture education. Traces of this influence can be detected by examining teaching course books of any architecture teaching institution, many western teaching institutions has developed tools for detecting theses influences, the (STAUNCH tool) is used to trace the level of engaging sustainability principles in Salahaddin University teaching program. The paper managed to elaborate an assessment of Salahaddin University architecture teaching program status in terms of availability of sustainability principles, and raised some notes and recommendation on how to develop teaching programs to go with UIAaim (architecture for a sustainable future)